2021
DOI: 10.3390/ijerph182312286
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Level of Technical and Tactical Skills and Its Relationships with Aerobic Capacity and Special Fitness in Elite Ju-Jitsu Athletes

Abstract: Background: Ju-jitsu training has to be comprehensive in terms of training intensity, developing a wide range of physical fitness and learning multiple technical skills. These requirements result from the specificity of the competition characteristic of the sport form of this martial art. The aim of this study was to evaluate the aerobic capacity and special physical fitness of ju-jitsu athletes at the highest sports performance level and to determine the relationships between special fitness and the indices o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
0
8
0
2
Order By: Relevance
“…Female Brazilian Jiu-jitsu (BJJ) practitioners are growing, and the demand for scientific studies generating gender-specific training approaches is needed. An inclusive understanding of the time-motion combat demands of female combat athletes could positively impact the success rate and help in training efficiency ( Williams et al, 2019 ; Ambroży et al, 2021 ; Pawelec et al, 2022 ). The performance in grappling combat sports is related to the ability of female or male competitors to execute specific actions at the right moment during each combat phase while quickly adjusting to the continually changing combat context to the following action or phase ( Sterkowicz-Przybycień et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Female Brazilian Jiu-jitsu (BJJ) practitioners are growing, and the demand for scientific studies generating gender-specific training approaches is needed. An inclusive understanding of the time-motion combat demands of female combat athletes could positively impact the success rate and help in training efficiency ( Williams et al, 2019 ; Ambroży et al, 2021 ; Pawelec et al, 2022 ). The performance in grappling combat sports is related to the ability of female or male competitors to execute specific actions at the right moment during each combat phase while quickly adjusting to the continually changing combat context to the following action or phase ( Sterkowicz-Przybycień et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results correspond positively with the measurements of sports jiu-jitsu athletes. Ambroży [ 38 ] showed that jiu-jitsu competitors who perform a lot of gripping actions presented a strength advantage in this aspect compared to karatekas, who were characterized by significantly less frequent gripping, with the prevalence of punches and kicks, similarly to Muay Thai competitors. A high level of development of this motor aspect among grapplers and wrestlers compared to strikers was also shown by Adamczyk et al [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the training process for the cadet age group must be adjusted to the training period in the long-term plan, the level of individual motor abilities, and the experience of the athlete. Moreover, it is very important to conduct mental preparation within the training process in the cadet age group, which often determines the effect of undertaken efforts, judo fights, as well as the regeneration process [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%